ХЯТАДЫН БАРУУН ХЯЗГААРЫН АЙМАГ УГСААТНЫ ТҮҮХ СОЁЛЫН ТУХАЙД - Ж.НАМКАМЯДАГ (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2002)
This paper studies the influence that Mongolia had after it had dominated the West Boarder Provincial XI YU/ where the politics, economy, culture and structure of nationalities were affected. Because of the Mongolia rule that had dominated the West Boarder Provincial /XI YU the feudal separatist rule was ended and they had to give control over this area to those within the united state. So the economy developed and Islam was popularized. The above shows how the conditions under which the united Uigur nationality was formed.